2012
DOI: 10.1302/0301-620x.94b2.27470
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and late complications of percutaneous epiphysiodesis with transphyseal screws

Abstract: Percutaneous epiphysiodesis using transphyseal screws (PETS) has been developed for the treatment of lower limb discrepancies with the aim of replacing traditional open procedures. The goal of this study was to evaluate its efficacy and safety at skeletal maturity. A total of 45 consecutive patients with a mean skeletal age of 12.7 years (8.5 to 15) were included and followed until maturity. The mean efficacy of the femoral epiphysiodesis was 35% (14% to 87%) at six months and 66% (21% to 100%) at maturity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 27 publications
1
78
0
3
Order By: Relevance
“…Given the improved cosmesis, decreased operative time, and reduced recovery time, percutaneous fluoroscopic-assisted epiphysiodesis has become the recommended method for treating moderate LLD [2,5,7,[10][11][12][13][14]. Multiple studies have demonstrated the efficacy and safety of percutaneous epiphysiodesis since its introduction in the 1980s [5,7,[10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Rates of incomplete physeal ablation have been shown to be similar (15%) for both open and percutaneous techniques for epiphysiodesis [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the improved cosmesis, decreased operative time, and reduced recovery time, percutaneous fluoroscopic-assisted epiphysiodesis has become the recommended method for treating moderate LLD [2,5,7,[10][11][12][13][14]. Multiple studies have demonstrated the efficacy and safety of percutaneous epiphysiodesis since its introduction in the 1980s [5,7,[10][11][12][13][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Rates of incomplete physeal ablation have been shown to be similar (15%) for both open and percutaneous techniques for epiphysiodesis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple studies have demonstrated that percutaneous epiphysiodesis offers decreased complications compared with the traditional open Phemister technique, a revision rate of nearly 20% has been reported [15]. Percutaneous epiphysiodesis using transphyseal screws (PETS) has also been described; this is accomplished without curettage of the physis.…”
Section: Endoscopic-assisted Epiphysiodesis Ledesma Et Al 27mentioning
confidence: 99%
See 2 more Smart Citations
“…Автор описував цю техніку як малотравматичну, що має низький відсоток ускладнень. Ефективність використання гвинтів була продемонстрована рядом авторів, які отримали пози-тивні результати при корекції помірної РДНК [30,36,50,61].…”
Section: рисунок 1 техніка відкритого епіфізеодезу за Phemister рисуunclassified